Between Immortal and Man: A Colonialism and Post-Colonialism Analysis in Superman (2025) Movie - Putra, Jonathan Syah; Nathanael, Jeshua; Wijaya, Josh Fitzkioshi; Rustandar, Evan Denzel; Ang, Michelle Whitney; Runtuwen, Zefanya Christania Evangelina (Yayasan Pendidikan Gereja Masehi Advent Hari Ketujuh Makarios, 2026)
The purpose of the work was to investigate the Superman (2025) movie, by employing a postcolonial approach to show how the movie creates the concepts of identity, the rules of power, and cultural identity in modern society. Within a qualitative approach, the study used scene based textual analysis, narrative sequence close reading, and visual analysis of cinematography as the main methods of data collection. This methodology involved the interpretive analysis of dialogue, interaction of characters, political symbolism and media representations in order to discover how the postcolonial tensions, instilled in the movie. Based on a theoretical framework formulated by Homi K. Bhabha (1994/2004), the concept of hybridity, mimicry, ambivalence, and the Third Space, the paper studied Superman as a hybrid character who struggles with opposing identities between his kryptonian heritage and human origins. The findings: 1) Superman is not depicted as a unified national hero but as a form of ambivalent subject, shaped by the plays of hybridity; 2) Lex Luthor thus represents Bhabha, the mimicry, as it employed imitation, technological reproduction and performance to challenge a superior Other; and 3) the film demonstrates heroism as a moral cultural struggle not a physical one, subversing the discourse of traditional hegemonies. The paper concludes that the Superman (2025) movie introduces the superhero as a colonizer and colonized, exposing interstrata tension of belonging, power, and resistance in the world of the film. The study contributes to the modern postcolonial discussion in popular cinematography and that the future research may conduct the comparative analysis of other texts of superheroes, how the audience receives postcolonial images, or how the theme of hybrid identity becomes reflected in the world media.